Social media impact on public attention: Paris Olympics case study - Mingyang Zhang; Yuyue Liao (PLoS ONE, 2025)
Large-scale sports events yield multi-dimensional positive benefits for urban development, and analyzing their spatiotemporal characteristics is crucial for scientific decision-making. However, existing studies focus on long-term effects, lacking detailed quantitative analysis of short-term dynamics, driving mechanisms, and geographical patterns of attention for single large-scale events using the latest data. Taking the 2024 Paris Olympic Games as a case, this study employs Baidu Index data, hot spot analysis, regression analysis,to explore spatiotemporal characteristics and relational mechanisms of Chinese public and media online attention. Results show: (1) Public and media attention exhibits temporal patterns of pre-event rise, in-event peak, and post-event decline, highly correlated with key competition days; (2) Spatial distribution presents an “east-high, west-low” pattern, with hotspots concentrated in eastern coastal areas; (3) Media attention significantly drives public attention positively, but its influence intensity varies regionally. This study reveals short-term dynamics and spatial differentiation mechanisms of large-scale sports attention in the social media era, providing theoretical and practical references for optimizing communication strategies and enhancing public participation.